Origen, conformación y fin de un sistema agroecológico: los solares sustentables de la Mixteca Alta de México - J. Edgar Mendoza García (Caravelle)
This paper analyzes the origin, development and decline of Mixteca Alta’s agroecological and food system from the end of pre-Hispanic period till capitalism’s introduction, in the context of the Great acceleration which appeared indirectly in this region during the middle of the 20th century, when new roads were opened allowing local populations’emigration towards towns and industrial centers, that lead to the almost complete disapperance of sustainable “solares” (vegetable gardens) and the rapid expansion of food practices different from local diets.